Enhancing Laboratory and Nursing Practices through Interdisciplinary Collaboration in Clinical Settings - Abdulaziz Fahad Alotaibi; Abdulrahman Saad Mohammed Alabdulkarim; Sawsan Abdullah Mohammed Almofarij; Modi Saud Mohammed Alqahtani; Hasan Saleh Alohideb; Abdulaziz Mohamad Ibrahim Alfayz; Dalal Mohammed Alsoaidan; Rogayah Abdalaziz Hamad Almofarij; Majed Saud Mohammad Alkahtani; Maher Mohammed Alsoaidan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Interprofessional collaboration between nurses and laboratory professionals improves patient care and health outcomes. This is because clinical and laboratory skills are put together to enhance diagnosis accuracy, timely intervention, enhancing patient satisfaction, among other established benefits, which are quite opposite to the presenting challenges that include communication barriers, misunderstanding of professional roles, and the need for integration of technology. Now, it is necessary to have a nursing and laboratory interdisciplinary collaborative approach; communication strategies underpin this, the role of technology, shared training, leadership, support, and models of care centred on the patient are discussed. It also provides recommendations to reinforce collaboration with a view to meeting new challenges presented to the health system.